Perception of cancer patients on the influence of spirituality in chemotherapy treatment - Mesquita, Izabelle Mara Rodrigues (2019)
This study aims to describe the perception of cancer patients on the spirituality influence on chemotherapy. This is a qualitative research with eight adults and elderly patients. Data were collected in November 2017, through a semi-structured interview and two guiding questions. The information extracted from the interviews were analyzed using the Discourse of the Collective Subject method. Two speeches emerged: hindering aspects for the understanding of spirituality and acceptance of the disease, aid for healing and self-help. Spirituality needs to be addressed with patients and better worked in the training of health professionals, as it is a way of coping with the disease, diminishing suffering acquired through faith and hope.